Marked improvement in leptomeningeal carcinomatosis and spinal cord metastases following alectinib treatment of crizotinib-resistant, ALK-positive lung adenocarcinoma - Kuribayashi, Hidehiko (Int Cancer Conf J, 2015)
We report a case of 50-year-old Japanese female with anaplastic lymphoma kinase (ALK)-positive, crizotinib-resistant lung adenocarcinoma, whose leptomeningeal carcinomatosis and spinal cord metastases were dramatically improved by the second-generation ALK inhibitor alectinib. Magnetic resonance imaging (MRI) revealed multiple brain metastases at diagnosis of lung cancer. Carboplatin/paclitaxel/bevacizumab chemotherapy was administered, but enlargement of brain tumors was observed after 3 months. Gamma knife radiosurgery was performed and then the patient received second-line chemotherapy with crizotinib. After 4 months brain MRI revealed the development of leptomeningeal carcinomatosis. Despite the patient undergoing whole brain radiotherapy, spinal cord metastases appeared. Third-line chemotherapy with alectinib was initiated for the management of metastases in central nervous system (CNS) including those in the leptomeninges and spine cord. After 3 months, marked tumor responses were observed in both the leptomeningeal carcinomatosis and spinal cord metastases. This report suggests that alectinib is a promising drug for ALK-positive lung adenocarcinoma with CNS metastases.